Islamic Education and its Value: A Vital Means for the Formation National Character - Umar Abdullahi Maidugu; Adamu Tanko Isah (Bulletin of Islamic Research, 2024)
This study examines the significance of Islamic education in forming national character. By exploring the historical context, conceptual framework, and values of Islamic education, this research demonstrates the vital role of Islamic education in shaping the character, values, and worldview of individuals and communities. The study argues that Islamic education provides a moral and spiritual foundation for individuals and societies, promoting integrity, justice, compassion, responsibility, and unity. The results of the study show that Islamic education consistently educates values such as honesty, responsibility, truth, justice and respect for others, which are very important in the formation of individual character with integrity. Islamic education also plays a role in strengthening students' cultural and religious identity, promoting tolerance, mutual respect and social solidarity amidst the cultural and religious diversity of Nigerian society. Not only that, the integration of modern knowledge and life skills in the Islamic education curriculum ensures that individuals develop not only moral qualities but also relevant competencies to face global challenges. However, challenges such as limited competent human resources, relevance of the curriculum to the needs of the times, and lack of funds and infrastructure, are obstacles that need to be overcome. The findings of this research have implications for education policymakers, practitioners, and scholars seeking to promote holistic and balanced education that fosters national character and social cohesion.